2014
DOI: 10.1136/bmjopen-2014-006713
|View full text |Cite
|
Sign up to set email alerts
|

Historical cancer incidence and mortality assessment in an Illinois community proximal to a former manufactured gas plant

Abstract: ObjectivesConcern has been raised that the occurrence of cancer may be increased in neighbourhoods around a former manufactured gas plant in Champaign, Illinois, USA. Thus, we compared historical rates of cancer in this area to comparison communities as well as with nationally standardised rates.DesignRetrospective population-based community cancer assessment during 1990–2010.SettingChampaign County, Illinois, USA, and zip codes encompassing the location of the former manufactured gas plant to counties that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Twelve studies showed that exposure to air pollution was associated with increased risk for kidney-related outcomes. Three studies reported that exposed populations had a lower risk of kidney cancer [ 31 , 36 , 37 ]. One study reported no significant difference in the risk for hypertension or diabetes between exposed and unexposed populations [ 33 ], while the remaining nine studies reported mixed findings.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies showed that exposure to air pollution was associated with increased risk for kidney-related outcomes. Three studies reported that exposed populations had a lower risk of kidney cancer [ 31 , 36 , 37 ]. One study reported no significant difference in the risk for hypertension or diabetes between exposed and unexposed populations [ 33 ], while the remaining nine studies reported mixed findings.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only a small number of these epidemiological studies has been completed, including one that identified significant effects of TCE exposure on birth outcomes in New York (Forand et al., 2012), and one that identified no increase in cancers associated with a gasworks site in Illinois (Alexander et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The most direct way of rating health risks would be to carry out extensive epidemiological studies on health effects associated with contaminated sites, but these studies T A B L E 1 Continued are notoriously complex and difficult to complete (Hoek et al, 2018). To date, only a small number of these epidemiological studies has been completed, including one that identified significant effects of TCE exposure on birth outcomes in New York (Forand et al, 2012), and one that identified no increase in cancers associated with a gasworks site in Illinois (Alexander et al 2014).…”
Section: Risk Profile Of Contaminating Activitiesmentioning
confidence: 99%